Effects Of The Entry Of Immigrants To Colombia On International Flights On The Hotel Occupancy Rate: A Regression Analysis - Parra, John Buelvas; Babilonia, Lorena Hoyos; Nuñez, William Niebles (Migration Letters, 2023)
This research revolved around the analysis of the influence of the entry of immigrants to Colombia through international flights on the hotel occupancy rate in Colombian territory. This analysis consisted of a simple linear regression model structured by the entry of immigrants as an independent variable and hotel occupancy as a dependent variable. The observations were collected from data collected from the website of the Ministry of Commerce, Industry and Tourism (MINCIT) and the National Administrative Department of Statistics (DANE), delimited between January 2021 and November 2023. The results obtained demonstrated the existence of a significant correlation between the variables studied, serving as a starting point for the subsequent results, defined by the regression equation Y = 30.8 + 0.00003287X, where Y represents the hotel occupancy rate in the Colombian territory and immigrants who arrive in Colombia through international flights. The simple linear regression model generated had a significant slope, with a P value of 4.66×10-9, much lower than the significance level of 0.05, while the R2 value of 0.6411 indicated that the model obtained explained 64.11% of the variation in hotel occupancy within the time period studied. Finally, the results of testing the assumptions of linearity, normality, and homoscedasticity indicated that the relationship between the variables is linear, the residuals are normally distributed, and the variance of the residuals is constant at all levels of the response variable. These results contribute to understanding the dynamics of immigration and tourism in Colombia, making clear the need for a comprehensive analysis when evaluating the factors that determine hotel occupancy rates.